Voices and Practices in Applied Linguistics Diversifying a Discipline - Wright, Clare; Harvey, Lou; Simpson, James (White Rose University Press, 2019)
"Voices and Practices in Applied Linguistics comprises a selection of original applied linguistics-based research on the theme of the diversity of Applied Linguistics and in Applied Linguistics. It is a unique collection of reflections and cutting-edge research relating to academic, policy and professional fields of Applied Linguistics, featuring chapters written by founders of the field, established researchers, and rising stars. This accessible, eclectic and forward-looking volume is significant both for research and practice. It highlights current globalised perspectives on diversity in language use and communication, across a variety of contexts, and with a rich mix of frameworks, methodologies and participants. Compiled and edited by a team of academic experts in the field, this edited collection will be of interest to established and emerging researchers in Applied Linguistics globally. It will also be relevant to language professionals, practitioners, and policy makers. The volume draws together papers from the 2017 British Association for Applied Linguistics (BAAL) conference, marking the 50th anniversary of its inaugural meeting. Founded in the mid-1960s, this UK-based professional association provides a forum for Applied Linguistics and its annual meeting brings together researchers and language professionals from across this field."